Mechanical properties and microstructure of vacuum plasma sprayed Cr3C2 – 25(Ni20Cr) coatings - Mrdak, Mihailo R. (Vojnotehnički glasnik / Military Technical Courier, 2014)
This paper analyzes vacuum plasma spray VPS - Cr3C2 - 25(Ni20Cr) coatings. Commercial powder marked Sulzer Metco Woka 7205 is used. The powder is deposited with a plasma gun F4 at a distance of 340 mm from the substrate. The main objective of the study was to eliminate, at the reduced pressure of inert gas Ar, the degradation of primary Cr3C2 carbide into Cr23C6 carbide which significantly reduces the microhardness and mechanical properties of the coating. The coating is deposited with a thickness of 100 - 120 µm on a steel substrate. The microhardness of the coating was tested by HV0.3. The microhardness values were in the range of 1248 - 1342 HV0.3. The bond strength of the coating was tested by tension. It was found that the bond strength between the substrate and the coating has a value of 89 MPa. The microstructure of the coating was tested by the light microscopy technique. The structure of the coating consists of an NiCr alloy base with a dominant primary Cr3C2 carbide phase. In addition to the Cr3C2 phase, the Cr7C3 phase is also present. The coating etching was done with the reagent 1HNO3 : 4HCl : 4H2O that primarily dissolves nickel to enable the distribution of the carbide phase to be clearly seen in the coating. Etching the coating with this reagent revealed the presence of the largely undegraded primary Cr3C2 carbide phase which provides high hardness values to the coating.